Spatial Synchronization and Territorial Planning Policies between Regions and National Spatial Planning - Sri Kusriyah (Jurnal Daulat Hukum, 2021)
This study aims to determine whether the spatial and regional policies in the regions are in sync with the national spatial planning arrangements. The method used in this research is using a normative juridical research method, with the main data being secondary data in the form of documents related to regional spatial planning policies in the region, then the data is analyzed by qualitative analysis by providing an interpretation of the data that has been collected. The results show that the regional policy of Demak Regency in spatial planning as outlined in the form of a regional regulation with the aim of realizing regional space based on superior agricultural and industrial sectors, supported by the service trade and tourism sectors that are environmentally sustainable, refers to the Act. Number 6 of 2007, and Act No. 11 of 2020 concerning Job Goals, Government Regulation number 26 of 2008.The Regional Regulation on RT/RW regulates, among others: a) spatial planning policy, b) spatial planning strategy, c) spatial structure plan, d) spatial pattern plan, e) determination of strategic areas, f) spatial utilization direction, g) spatial utilization control direction, h ) rights, obligations and roles of the community, i) institutions, thus the policy for structuring spatial planning in the sub-region is in sync with the structuring of national spatial plans